Microbiological Examination Of Uterine Secretion In Cows With Mastitis (Texas Journal of Agriculture and Biological Sciences, 2026)
In this article, the main composition of microorganisms isolated from mastitis of dairy cows is Candida+Staphylococcus aureus+Streptococcus agalaetiae fungi and staphylococci; Staphylococcus aureus+Streptococcus agalaetiae; Streptococcus dysgalaetiae+Staphylococcus haemolyticus; Staphylococcus epidermidis+Escherichia staphylococci and streptococci; Candida species Coli+fungi; Staphylococcus epidermidis+Clostridium perfringens are staphylococci and clostridia, including Streptococcus agalaetiae (27%), Staphylococcus aureus, Staphylococcus hominis, Staphylococcus saprophyticus, Escherichia Coli (4%), Streptococcus dysgalaetiae, Clostridium perfringens (3%).